Hackelselängden beroende av skördemetod - Ambjörn, Marcus; Lagerstedt, Per (2005)
The conditions for a good silage process start with good wheather and choice of crop, then choice of harvesting machinery. The shorter and more mechanically treated crop, the better quality of the forage. (Pauly 1994). This study has examined the variations in chopping length depending on harvest method. Precision choppers works with a rotating chopping cylinder, where the crop is cut into pieces. The crop flow into the cylinder is determined of the specific speed of two rolls, which has influense of the chopping length. Silagewagons works with a fixed chopping length, which is determined of the distance between the knifes. The distance is the same on both waggons in this study. Samples has been taken out and then sorted after length. The length fractions in the model was <20 mm, 20 - 40 mm, 40 – 60 mm, 60 –100 mm and >100 mm. To be able to decide dry matter and weigh percent the different fractions were put in scale bowls. Before the sorting all of the sample were weighed. The results of this study shows that choppers have a very big amount of forage in that fraction which the machinery is adjusted for. Both choppers are able to maintain their mainly chopping length under 40 mm. The JF-chopper had most of forage in the interval 20-40 mm. They were adjusted for 12, respectively 14 mm but can be adjusted down to 5, respectively 4 mm chopping length. Silagewagons have more longer straw materials than the choppers. That is because of the construction, which only makes it possible to cut it in 35 mm. Even though they have cut twice as long, they cut the silage to an acceptable length. In difference to the precision choppers, the silagewaggons distribute the silage more between the fractions. The biggest sample is in the fraction 40 – 60 mm. They have the same differ from the theoretical chopping length as the choppers, even though the choppers are able to process the silage shorter. Pöttingers silagewagon can carry 22 m3 extra per load compared to the Sahlströms equipage. That means that 30 % less loads needs to be transported from the field. It halves the cost from windrow to silo, based on our calculation. It is important what adjusted value of chopping length means in the reality, when the real value seems to be longer than the adjusted. On a silagewagon the chopping length can be longer by taking away knifes but that is hardly desirable when you want it as short as possible. A chopper has the ability to cut much shorter pieces of the forage but has a several more adjustment possibilities to observe. Often you set the machine for one cutting length and then adjust it again if the result isn´t acceptable. Generally for these different kind of harvest machinery is that it is very important to keep the knifes sharp. The conclusion after the study is that choppers are most suitable for bunker silos, because of that the silage is properly processed and does only need good cover and packing to achieve high silage quality. Shortcut carriages are more suitable for silaging in a tube or in a towersilo. In a tube the forage is processed further by a packing roll, in a towersilo the crop is processed by a throw fan.